Mauritius : Staff Report for the 2019 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation discusses that Mauritius is pursuing an ambitious strategy to foster inclusive growth and reach the high-income country milestone. Several structural challenges, notably, a shortage of suitably skilled workers, an aging population, and declining productivity and cost competitiveness confront Mauritius in meeting these goals. The discussions focused on preserving fiscal sustainability, regaining external competitiveness, and maintaining financial integrity and stability. Several steps have been undertaken to boost skill development, improve the business climate, and build innovation capacity. On the expenditure side, economic activity is expected to be spurred in the near term by public spending on infrastructure projects and sustained in the medium term as those projects and productivity-enhancing reforms improve private-sector competitiveness. It is recommended to pursue fiscal consolidation from the forthcoming budget FY2019/20 to build fiscal credibility and set public debt firmly on a declining path into the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet